Microextraction and Eco-Friendly Techniques Applied to Solid Matrices Followed by Chromatographic Analysis - Attilio Naccarato; Rosangela Elliani; Antonio Tagarelli (Separations)
In this review, a 5-year overview on environmentally friendly approaches for the extraction of the most relevant organic pollutants in soil, sediment, particulate matter, and sewage sludge coupled with chromatographic analysis is reported. Organic contaminants encompass various compounds derived from personal care products, industrial chemicals, microplastics, organic matter combustion, agricultural practices, and plasticizer material. The principles of green analytical chemistry (GAC) and green sample preparation (GSP) serve as a guideline for the development of more environmentally sustainable analytical protocols. This study focuses attention on microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), matrix solid-phase dispersion (MSPD), and microextraction techniques, such as solid-phase microextraction (SPME), stir bar sorptive extraction (SBSE), hollow-fiber liquid-phase microextraction (HF-LPME), spray-assisted droplet formation-based liquid-phase microextraction (SADF-LPME), and dispersive liquid–liquid extraction (DLLME). These approaches represent the most relevant eco-friendly sample preparation for the advanced extraction of target analytes from environmental solid samples.